2020
DOI: 10.1016/j.radi.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Competencies of therapeutic radiographers working in the linear accelerator across Europe: A systematic search of the literature and thematic analysis

Abstract: a b s t r a c tIntroduction: The literature identifies various competences required for therapy radiographers (TR), however, these are varied and scattered among different publications. The aim of this study was to identify the competences required by therapy radiographers practising on the linear accelerator in the European setting, according to published literature. Methods: A systematic approach was performed to find relevant literature. The literature was then scrutinised for competences practised by linac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…New aspects in MRIgRT require planning experience, particularly for UK radiographers where dosimetry experience is lacking, as other professions dominate the field or require specialist radiographers. 33 , 34 , 35 , 36 Yet, in countries where radiographers have dosimetry experience, additional image recognition and contouring was required. Little documentation exists surrounding MRI education to specialist groups and post-graduation education has been suggested previously 37 , 38 as opposed to current on-the-job learning and teaching.…”
Section: Discussionmentioning
confidence: 99%
“…New aspects in MRIgRT require planning experience, particularly for UK radiographers where dosimetry experience is lacking, as other professions dominate the field or require specialist radiographers. 33 , 34 , 35 , 36 Yet, in countries where radiographers have dosimetry experience, additional image recognition and contouring was required. Little documentation exists surrounding MRI education to specialist groups and post-graduation education has been suggested previously 37 , 38 as opposed to current on-the-job learning and teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this disparity is more evident in non-technical competencies (such as Management and leadership), it was also observed in technical competencies (such as Equipment quality assurance and Image verification of patient setup). These results showed that some competencies identified in the literature as being the responsibility of the TRs 18 are not fully developed across the EU. As such, these disparities have the potential to become an issue when movement occurs, and further research should be performed.…”
Section: Uniformity Of Radiotherapy Education In the Eu (Or Lack Thermentioning
confidence: 90%
“…In the second part, the respondents were asked to score how competent graduates are at the end of the programme. They were invited to rate 63 competencies related to the linac, organised under 14 competency dimensions 18 ( Table 1). The selection of the competencies was based on an analysis of the literature, results from previous research performed by this research team 18 and feedback from expert partners within the SAFE EUROPE project.…”
Section: Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent role of these professionals is the delivery of ionising radiation to treat patients 11 ; however, to perform this role, TRs must develop competencies in multiple areas, including immobilisation of the patient, imaging, decision-making, education, communication, and research, among many others. 12 There are also differences in the nomenclature due to a lack of harmonisation of the professional title, a range of national titles such as Therapeutic Radiographer (TR), Radiation Therapist (RTT), Radiotherapist, Radiation Therapy Technologist may also be found in the literature 9,13e15 and mentioned by the study participants in this study.…”
Section: Introductionmentioning
confidence: 92%